(untitled) (Journal of Advanced Research in Social Sciences, 2025)
Argentine political instability is a subject of ongoing study in the scientific literature. Argentina is seen as a paradox, a nation that does not exhibit political stability in accordance with its level of socio-economic development. This paper demonstrates that the primary cause of political instability is a widespread contempt for authority throughout Argentine society, originating during the period of the Spanish conquest and colonization of the Americas and passed down from generation to generation to the present day. This claim is substantiated through a meta-analysis of historical, genetic, and legal information, where a set of propositionally logical statements derived from factual analyses is used to establish the causality of mathematical relationships between groups of genetic and legal data. The study is complemented by a set of solutions based on the entire analysis, taking into account social factors for each specific case.